Penerapan Model Pembelajaran Remedial Berbasis Nilai Islam: Penelitian - Arini Rahman; Muslim Afandi; Mhd Subhan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses the implementation of remedial learning models innovated with Islamic values as an approach to improve students' achievement and character. Remedial learning is generally used for students who experience academic difficulties, and integrating Islamic values is a strategic effort to strengthen spiritual and moral character. Through this approach, education does not only focus on cognitive aspects, but also on affective and spiritual aspects. The literature review method was used to evaluate relevant national and international scientific journals as the main reference in formulating this model. Results show that Islamic value-based remedial learning is effective in improving students' learning motivation, achievement, and shaping their religious character.